The next global stage challenges and opportunities in our borderless world - Ōmae, Kenʾichi. (Upper Saddle River Wharton School Pub, 2005)
Globalization is a fact. You can't stop it; it has already happened; it is here to stay. And we are moving into a new global stage.
Includes bibliographical references and index.
Keywords: International economic integration